Exploring the mechanisms of anti-ovarian cancer of Hedyotis diffusa Willd and Scutellaria barbata D. Don through focal adhesion pathway. (28th October 2021) - Xu, Xiao; Chen, Fenglin; Zhang, Lin; Liu, Likun; Zhang, Cuili; Zhang, Zhiwei; Li, Weiling
Abstract: Ethnopharmacological relevance: Hedyotis diffusa Willd and Scutellaria barbata D.Don (HD-SB) pairing were widely used as traditional medicine known for their anti-tumor effects. However, the inhibitory effect of HD-SB on ovarian cancer and its potential mechanisms were still not clear. Aim of the study: Our study identified the anti-tumor effect of HD-SB on ovarian cancer and analyzed the potential mechanisms by the network pharmacology and molecular docking method. Materials and methods: The inhibitory effect of HD-SB combination on the growth and migration of ovarian cancer was detected by MTT and transwell assays. The effective ingredients of HD-SB and their potential targets were obtained from the Traditional Chinese Medicines for Systems Pharmacology Database (TCMSP), the GeneCards database, and the UniProt database. The relationships between active ingredients of HD-SB and potential targets or pathways of ovarian cancer were analyzed by String database, Cytoscape 3.7.2 software, and David 6.7 online database. The anti-ovarian cancer targets of HD-SB in the focal adhesion pathway were identified by RT-qPCR and molecular docking. Results: HD-SB combination significantly inhibited the proliferation and migration of ovarian cancer cells. We observed that the 1:2 ratio of HD-SB had the lowest IC50 value. 60 gene targets of 33 active ingredients in HD-SB were selected by pharmacokinetic parameters. The network pharmacological analysis showed that quercetin, luteolin, and baicalein might be the important anti-ovarian cancer ingredients in HD-SB, and the inhibitory effects of these three ingredients on the proliferation of ovarian cancer cells were verified respectively. Functional enrichment results suggested that HD-SB inhibited ovarian cancer growth and migration mainly through the focal adhesion pathway and the potential targets were EGFR, MAPK1, VEGFA, and PIK3CG. Conclusions: HD-SB pairing significantly inhibited the proliferation and migration of ovarian cancer. Using network pharmacological methods and validation experiments, we found that HD-SB might, at least partially, inhibit ovarian cancer through the focal adhesion pathway. We believed that the HD-SB combination could be a potential therapeutic drug for the treatment of ovarian cancer patients. Graphical abstract: Image 1 Highlights: HD-SB inhibited the proliferation and migration of ovarian cancer. Quercetin, luteolin and baicalein were the main anti-ovarian cancer ingredients of HD-SB. HD-SB inhibited ovarian cancer at least partially by regulating EGFR, MAPK1, VEGFA and PIK3CG in the focal adhesion pathway.